Distributed control for voltage and current sharing islanded DC microgrids under cyber attacks - Lim, Hui Jing (Nanyang Technological University, 2021)
As a cyber-physical system (CPD), a microgrid (MG) is threatened by various cyber-attacks. To ensure the security of MGs under these attacks, suitable control method must be designed to enhance the security of MG. Technology has improved drastically over the years and people are getting more dependent on them and it can be dangerous as malicious entity can hack into the system, causing severe consequences in sensitive sites such as military bases and hospitals. Sensitive information can be taken away and resulting in great danger. A cyber security detection technique, Kullback-Liebler divergence-based criterion, is being investigated and verified in this this report. The purpose of this technique is to distinguish any irregular behavior of a Distributed Energy Recourse (DER) control unit that is being compromised, by calculating the interior and exterior belief factor. The interior belief factor is calculated and used to communicate with its adjacent DERs to inform them on the accuracy of its outgoing information. On the other hand, by calculating the exterior-belief values, it ensures the accuracy of the information that is being received from its adjacent DERs. By using the calculations of the interior and exterior belief values, it will show down and mitigate attacks. Connection network with mild graph connectivity is required for this proposal. A conventional medium voltage DC microgrid system is stimulated to verify the authenticity of the Kullback-Liebler divergence-based criterion technique. It is proven that by using this technique, the voltage of the buses of the microgrid is well controlled and DERs are able to recognize cyber-attacks during legitimate occurrences successfully. The purpose of this Final Year Project (FYP) is to develop a suitable method to tackle this problem. MATLAB Simulink will be used to verify the validity of the report. This report will cover how the methods are being implemented into the systems and how they are beneficial.